2018
DOI: 10.1053/j.jfas.2018.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Routine Follow-Up Radiographs for Ankle Fractures Seldom Add Value to Clinical Decision-Making: A Retrospective, Observational Study

Abstract: Currently, the routine use of radiographs for uncomplicated ankle fractures represents good clinical practice. However, radiographs are associated with waiting time, radiation exposure, and costs. Studies have suggested that radiographs seldom alter the treatment strategy if no clinical indication for the imaging study was present. The objective of the present study was to evaluate the effect of routine radiographs on the treatment strategy during the follow-up period of ankle fractures. All patients aged ≥18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 13 publications
2
24
0
Order By: Relevance
“…However, other researchers have reported weak association between radiographic measurements and functional outcome measures in individuals with upper limb trauma [30] and elective foot surgery [31]. Whilst the association between radiographic outcome and patient perceived outcome has not yet been evaluated in individuals with ankle fracture, some researchers have questioned the value in performing routine follow-up radiographs for this injury, as they rarely initiate a change in management plan in the absence of patient reported symptoms [32]. This article demonstrates that radiographic outcome is still widely collected as a primary measure in this type of clinical trial without sufficient evidence that it has any association with patient perceived outcome in individuals with an ankle fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other researchers have reported weak association between radiographic measurements and functional outcome measures in individuals with upper limb trauma [30] and elective foot surgery [31]. Whilst the association between radiographic outcome and patient perceived outcome has not yet been evaluated in individuals with ankle fracture, some researchers have questioned the value in performing routine follow-up radiographs for this injury, as they rarely initiate a change in management plan in the absence of patient reported symptoms [32]. This article demonstrates that radiographic outcome is still widely collected as a primary measure in this type of clinical trial without sufficient evidence that it has any association with patient perceived outcome in individuals with an ankle fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Despite overarching current trends towards the use of PROMs in clinical research, this review demonstrates that objective and clinician assessed outcomes remain a commonly analysed primary outcome measure in clinical trials for this patient population. This is despite the lack of consensus on what features or measurements of radiographs are deemed to be important for functional outcome and the value of routine X-Rays in the clinical management of ankle fractures is currently being reviewed [32, 39].…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands, with a population of over 17 million, approximately €5 million is spent annually on radiography for patients with ankle fractures. This estimate is based on an incidence of 30,000 per annum [ 15 ], with three to four follow-up radiographs [ 16 ], at a cost of €50 per radiograph [ 17 ]. Various studies have questioned the value of routine radiographs obtained at the first outpatient clinic visit and at intermediate-to-late follow-up (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…after the initial 3 weeks) of operatively treated ankle fractures [ 18 , 19 ]. A recent retrospective analysis, involving a cohort of 528 patients with an ankle fracture, demonstrated that as few as 1.2% ( n = 11/928) of routine radiographs obtained after 3 weeks of follow-up led to a change in treatment strategy [ 16 ]. These results suggest that current imaging protocols for the follow-up of ankle fracture patients might not be cost-effective.…”
Section: Introductionmentioning
confidence: 99%
“…Choosing Wisely is committed to reducing the use of diagnostic tests, treatments, and procedures if there is evidence of overuse, potential harm, or significant and unjustifiable costs . Routine radiography in the postacute follow‐up of distal radius and ankle fractures (ie, after an initial follow‐up period of 4 wk) is an example of diagnostic imaging with questionable value …”
Section: Introductionmentioning
confidence: 99%